Fikih Minoritas: Suatu Kajian Teoretis - Nurhayati Nurhayati (AHKAM : Jurnal Ilmu Syariah, 2013)
Abstract: Fiqh for Minorities: a Theoretical Study. Fiqh for Minorities—which in Arabic is called Fiqh al-Aqaliyyât— is a fiqh model that maintains legal association of sharia and the dimensions of a particular community, namely minority Muslim communities in western countries. Fiqh for Minorities is a product of reinterpretation of the existing arguments on the basis of the benefit whichis the spirit of sharia. The designers of this fiqh are Taha Jabir al-’Alwani in his book, Toward a Fiqh for Minorities: Some Basic Reflection, and Yûsuf al-Qarâdawî in his book, Fî Fiqh al-Aqalliyât al- Muslimah. Fiqh for Minorities originated from the accumulation of the concerns of Muslim minority communities in western countries when it should be doing something related to their religion. This fiqh is designed to provide guidance and a handle on the things that are prohibited and permissible for Muslim minorities living in western countries to carry out their obligations as a Muslim.Keywords: fiqh, minority, shariaAbstrak: Fikih Minoritas: Suatu Kajian Teoretis. Fikih minoritas—yang dalam bahasa Arab disebut dengan Fiqh al- Aqalliyât—merupakan model fikih yang memelihara keterkaitan hukum shar‘î dengan dimensi-dimensi suatu komunitas tertentu, yaitu masyarakat minoritas Muslim di Barat. Fikih minoritas adalah sebuah produk hasil reinterpretasi atas dalil-dalil atas dasar kemaslahatan yang memang menjadi spirit syariah. Penggagas fikih ini adalah Tâhâ Jâbir al- ‘Alwânî dalam bukunya, Toward a Fiqh for Minorities: Some Basic Reflection dan Yûsuf al-Qarâdawî dalam bukunya, Fî Fiqh al-Aqalliyât al-Muslimah. Fikh minoritas lahir berawal dari akumulasi kegelisahan masyarakat minoritas Muslim di Barat ketika harus melakukan sesuatu yang berkaitan dengan keagamaan mereka. Fikih ini didesain untuk memberikan panduan dan pegangan tentang hal-hal yang dilarang dan yang boleh bagi minoritas Muslim yang tinggal di Barat untuk menjalankan kewajiban-kewajiban mereka sebagai seorang Muslim.Kata Kunci: fikih, minoritas, syariahDOI: 10.15408/ajis.v13i2.932